2011
DOI: 10.1128/jvi.00819-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype C Isolates with Wild-Type Core Promoter Sequence Replicate Less Efficiently than Genotype B Isolates but Possess Higher Virion Secretion Capacity

Abstract: Infection by hepatitis B virus (HBV) genotype C is associated with a prolonged viremic phase, delayed hepatitis B e antigen (HBeAg) seroconversion, and an increased incidence of liver cirrhosis and hepatocellular carcinoma compared with genotype B infection. Genotype C is also associated with the more frequent emergence of core promoter mutations, which increase genome replication and are independently associated with poor clinical outcomes. We amplified full-length HBV genomes from serum samples from Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 51 publications
(70 reference statements)
4
71
2
Order By: Relevance
“…One limitation of our study is that we only investigated one clone per genotype, although we note that our findings pertaining to replication of genotypes B2 and C2 were similar to those of a previous study (10). In contrast, another earlier study observed greater replication in genotype B2 than in genotype C2 (12). Taken together, these and our present studies suggest that it is not possible to make broad generalizations about HBV replication phenotype across genotypes and subtypes.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…One limitation of our study is that we only investigated one clone per genotype, although we note that our findings pertaining to replication of genotypes B2 and C2 were similar to those of a previous study (10). In contrast, another earlier study observed greater replication in genotype B2 than in genotype C2 (12). Taken together, these and our present studies suggest that it is not possible to make broad generalizations about HBV replication phenotype across genotypes and subtypes.…”
Section: Discussioncontrasting
confidence: 53%
“…A more recent study utilizing 1.28-fold copies of the HBV genome concluded that the HBV genotype D replicated at lower levels than the HBV genotype A, although HBV replication was again low in this study (11). Direct comparisons of the replication phenotype of genotypes B and C utilizing 1.24-mer clones (10) or tandem dimers (12) identified differences in the comparative replication phenotypes of genotypes B and C in these studies, with Sugiyama et al (10) identifying higher levels of DNA replication for genotype C than for genotype B, in contrast to the findings of Qin et al (12), who identified higher levels of DNA replication for genotype B. Genotype differences in virus secretion were also observed, with Qin et al observing higher levels of secretion for genotype C than for genotype B (12), in contrast to Sugiyama et al, who observed similar levels of virion secretion for genotypes B2 (Ba) and C (10). This suggests that it is difficult to generalize about the impact of replication phenotype observed in vitro on the differences in HBV natural history observed across HBV genotypes and subtypes.…”
contrasting
confidence: 55%
“…Particles in the pellet were resuspended in 1/100 the original volume with complete medium or phosphate-buffered saline (PBS) for storage at Ϫ80°C, and the genome copy number was determined by dot hybridization using serial dilutions of cloned HBV DNA of known concentration for calibration (30). Similar procedures were used to purify sHBV from viremic serum samples collected from chronic HBV carriers from Shanghai, China, for another study (31). Informed consent was obtained from patients, and the study was approved by Institutional Board and by the Recombinant DNA Committee of Rhode Island Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Covalently closed circular DNA (cccDNA) was extracted according to an established method (33). Virions were immunoprecipitated from culture supernatant by a combination of rabbit antipreS1 antibody (R271) and horse anti-Ad/Ay antibody according to established protocols (29,31). Virion DNA, intracellular replicative DNA, and cccDNA were detected by Southern blotting, while HBV RNA was detected by Northern blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation